PENYUSUNAN MATERI KONSEP DIRI SISWA KELAS X3 SMA NEGERI 5 PEKANBARU TAHUN AJARAN 2013/2014 - Sri Wahyuni; Zulfan Saam; Sardi Yusuf (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
Abtract: The lack of a positive self concept of students and limited material on the concept of self encourage researchers to conduct research on the development of the self concept of material preparation of students of class X3 SMAN 5 Pekanbaru. Research objectives 1). Composed material concept of self that is suitable for high school students in terms of clarity, aspects of the systematics, image support, new material, and completeness of the materials. 2) Knowing the quality of the material produced. using the method of research and development. Which acts as a validator is a supervising professor, lecturer, one of two supervising lecturers BK FKIP UR, teacher mentors, 6 friends of the associate PL-BKS, and 36 students of class X3 SMAN 5 Pekanbaru. The material self concept consists of 4 sub chapter, which 1).Understanding of the self-concept, 2). The types of self-concept. 3). Factors that influence self concept. 4). How to build and improve self concept. Quality of the material concept of self produced based on this aspect of the matter is the obvious clarity with X = 4,19 and the percentage 83,8%. Aspects of the systematics of material is systematically with X = 3.95 and percentage 79%. Aspects of image support is good with X = 3.78 and the percentage 75,6%. This aspect of the matter is the new material with X = 4, 10 and percentage of 82%. Aspects of the completeness of the material is very complete with X = 4.30 and percentage of 86%. And of the overall aspect of the matter is the good quality with X = 4.06 and percentage of 81,28%.Key words: Material of self concept